1997
DOI: 10.1097/00000374-199706000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Reinforced Responding by AA and ANA Rats Following the Sucrose-Substitution Initiation Procedure

Abstract: Ethanol-reinforced responding was initiated in male AA and ANA rats using the sucrose-substitution procedure. Before the initiation procedure, a homecage, two-bottle preference test was conducted. The rats were then trained to respond on an Fixed-Ratio 1 schedule with sucrose reinforcement. Over sessions, ethanol was added gradually to the sucrose solution as the concentration of sucrose was reduced until 10% ethanol (v/v) alone functioned as the reinforcer for lever pressing. The schedule of reinforcement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…And, indeed, in experiment 1 neonatal rats ingested equal amounts of ethanol and water from the surrogate nipple (i.e., no preference for ethanol was established), whereas only experience with ethanol resulted in subsequent attachment to the empty nipple. Therefore, the findings of experiment 1 confirm that preference for ethanol and its reinforcing efficacy in terms of further behavioral plasticity are not strongly correlated (Files et al, 1997Ritz et al, 1994;.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…And, indeed, in experiment 1 neonatal rats ingested equal amounts of ethanol and water from the surrogate nipple (i.e., no preference for ethanol was established), whereas only experience with ethanol resulted in subsequent attachment to the empty nipple. Therefore, the findings of experiment 1 confirm that preference for ethanol and its reinforcing efficacy in terms of further behavioral plasticity are not strongly correlated (Files et al, 1997Ritz et al, 1994;.…”
Section: Discussionmentioning
confidence: 58%
“…Animal research has revealed a relatively weak correlation between preference for ethanol (usually measured as intake of ethanol versus water) and the reinforcing efficacy of ethanol in operant models (Files et al, 1997Ritz et al, 1994;Samson et al, 1998). According to Samson (1987), it is conceptually difficult to establish ethanol as a reinforcer solely on the basis of oral self-administration with free access; ethanol can be determined as a reinforcer only when the animal's behavior can be changed by contingent presentation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Indiana alcohol-preferring (P) (e.g., Files et al, 1992Files et al, , 1993Murphy et al, 1989;Penn et al, 1978;Ritz et al, 1994a,b;Samson et al, 1998;Schwarz-Stevens et al, 1991), ALKO alcohol-accepting (AA) (Files et al, 1997;Sinclair, 1989, 1990;Ritz et al, 1986Ritz et al, , 1989a, and Indiana high-alcohol-drinking (HAD) (Ritz et al, 1994a,b;Samson et al, 1998) rats have been described to press a lever to obtain pharmacologically relevant amounts of ethanol, in most cases comparable with those consumed under the home cage, two-bottle regimen. In contrast, selectively bred ethanol-nonpreferring Indiana alcoholnonpreferring (NP), ALKO alcohol nonaccepting (ANA), and Indiana low-alcohol-drinking (LAD) rats have been reported to display minimal degrees of lever pressing for ethanol, consistent with their avoidance of the ethanol solutions under the two-bottle paradigm.…”
mentioning
confidence: 99%
“…To this aim, in the present study sP rats were trained to press a lever to gain access to ethanol. The study design also included rats from the sNP line, to possibly compare the self-administration behavior of the sP/sNP line pair with that, recently determined by Samson and colleagues under an identical setting, of P/NP (Samson et al, 1998), AA/ANA (Files et al, 1997), and HAD/LAD (Samson et al, 1998) line pairs. To facilitate this comparison, we conducted the present study by using an experimental procedure similar to that previously used by Samson and colleagues with P/NP, AA/ANA, and HAD/LAD rats (Files et al, 1997;Samson et al, 1998).…”
mentioning
confidence: 99%
“…However, studies that use limited access models of ethanol self-administration also have demonstrated higher ethanol intake with HAD rats compared with LAD rats Li et al, 1993;McKinzie et al, 1998;Ritz et al, 1994;Samson et al, 1998). It has also been demonstrated that additional rat lines selectively bred for high 24 hr ethanol intake also drink more 10% ethanol (Robledo et al, 1993) and sucrose-ethanol solutions (Files et al, 1997; under limited access conditions. We selected the first replicate line of HAD rats for this study because self-administration data indicated that their limited access sucrose-ethanol and ethanol intake might be more robust than intake of the second replicate line .…”
Section: Discussionmentioning
confidence: 99%